2018
DOI: 10.1371/journal.pone.0203798
|View full text |Cite
|
Sign up to set email alerts
|

Changes of body composition after valve surgery in patients with mitral valve disease

Abstract: BackgroundPatients with chronic heart failure have alteration in body composition as a reduction in fat mass, lean body mass and bone mass. However, body wasting in valvular heart disease and the impact of corrective valvular surgery on body composition has not been investigated.ObjectivesWe hypothesized that body wasting in severe mitral valve (MV) diseases is reversible through MV surgery.MethodsForty eight patients who were scheduled to undergo MV surgery were consecutively enrolled after excluding patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…With proper weight maintenance, patient can overcome adverse effect of PPM and may have better hemodynamics, despite PPM. In 2018, Kim et al [23] from Korea 48 patients who underwent MV surgery using simplified nutritional assessment questionnaire for appetite laboratory tests, echocardiography, and dual-energy X-ray absorptiometry before and 1 year after MV surgery. They found that post MV surgery, all patients had increased appetite and improved laboratory data.…”
Section: Discussionmentioning
confidence: 99%
“…With proper weight maintenance, patient can overcome adverse effect of PPM and may have better hemodynamics, despite PPM. In 2018, Kim et al [23] from Korea 48 patients who underwent MV surgery using simplified nutritional assessment questionnaire for appetite laboratory tests, echocardiography, and dual-energy X-ray absorptiometry before and 1 year after MV surgery. They found that post MV surgery, all patients had increased appetite and improved laboratory data.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 186 heart failure patients, both the CNAQ and SNAQ were shown to have construct validity and internal consistency validity (14). Additionally, a separate study of 48 patients undergoing mitral valve surgery concluded the SNAQ showed significant appetite improvement after one year of recovery from surgery (20). Another study of 99 patients undergoing aortic valve replacement found the SNAQ was able to detect those who were considered to be moderately malnourished (21).…”
mentioning
confidence: 99%